Optimizing rib width to height and rib spacing to deck plate thickness ratios in orthotropic decks. Issue 1 (31st December 2016) - Fettahoglu, Abdullah
Abstract: Orthotropic decks are composed of deck plate, ribs, and cross-beams and are frequently used in industry to span long distances, due to their light structures and load carrying capacities. Trapezoidal ribs are broadly preferred as longitudinal stiffeners in design of orthotropic decks. They supply the required stiffness to the orthotropic deck in traffic direction. Trapezoidal ribs are chosen in industrial applications because of their high torsional and buckling rigidity, less material and welding needs. Rib width, height, spacing, thickness of deck plate are important parameters for designing of orthotropic decks. In the scope of this study, rib width to height and rib spacing to deck plate thickness ratios are assessed by means of the stresses developed under different ratios of these parameters. For this purpose a FE-model of orthotropic bridge is generated, which encompasses the entire bridge geometry and conforms to recommendations given in Eurocode 3 Part 2. Afterwards necessary FE-analyses are performed to reveal the stresses developed under different rib width to height and rib spacing to deck plate thickness ratios. Based on the results obtained in this study, recommendations regarding these ratios are provided for orthotropic steel decks occupying trapezoidal ribs.